COMBINATION THERAPY OF MASSAGE AND TEMU IRENG HERBAL (Curcuma aeoruginosa Roxb.) TO INCREASE CHILD APPETITES AND FOOD INTAKE - Adianti, Myrna; Pramesti, Resti Ella; Puruhito, Edith Frederika (Journal of Vocational Health Studies, 2020)
Background: Appetite is a condition where a person has an urge to satisfy activities in eating. Lack of appetite in children is characterized by eating small portions, reluctant to refuse when it comes time to eat, take a long time to finish a meal, playing with the food, etc. Children are at the stage of high curiosity and very active, which mean the energy needed must be sufficient. If the energy and nutrition needs are not sufficient it might lead to a slowdown in physical and psychological growth. Purpose: The purpose of this case study is to observe whether Swedish massage and children's massage with a combination of Temu Ireng herba (Curcuma aeruginosa Roxb.) could increase appetite in school-age children. Result: The results of massage therapy with Temu Ireng decotion can increase appetite in children based on the increasing number of calories consumed before therapy from 1,267 kcal to 2,050 kcal per day after therapy session, and an increase in body weight of 0.9 Kg after 8 weeks of therapy. Conclusion: Providing Swedish massage therapy with a combination of Temu Ireng herba (Curcuma aeruginosa Roxb.) could increase appetite in schoolage children with the result of increasing the number of daily calories intake and body weight.